Industrial heritage along belgrade waterfront in planning documents / Индустријско наслеђе дуж београдског приобаља у планским документима - Nikolić, Marko; Vukmirović, Milena (Arhitektura i urbanizam, 2020)
The City of Belgrade is situated at the confluence of the Sava and Danube. Accordingly, this geographical position has strongly shaped Belgrade’s strategic and geopolitical significance, as well as its identity. In the last two decades, the development of several mega-projects in the area of Belgrade waterfront has had a negative impact on the cultural heritage of Belgrade and its historical cityscape, affecting its urban morphology and typology. The reason for this is that urban regeneration is most often driven by economic interests, while the preservation of meaning and the memory of a place are neglected. Along with these processes, several civic initiatives have emerged that aim to prevent damage to the built heritage and to indicate the need for stronger involvement of citizens in the city’s planning and development processes. In order to discontinue the tendency of being driven by economic interest and demonstrate a will to achieve further sustainable development, it is necessary to redefine the procedure for protecting valuable cultural heritage. This could be achieved by creating a new approach to protecting cultural heritage in the domain of urban design and planning, taking into account all the values, tradition, authenticity and identity of a place. Accordingly, the paper will focus on the issues of protecting Belgrade’s waterfront heritage, its historical and urban context, its genesis, and its cultural and architectural characteristics. Furthermore, the possibilities for different approaches to the presentation and modern utilization of the abandoned and ruined waterfront heritage will be investigated, in order to define new, common procedures that will be in line with city development goals, citizen expectations and heritage protection measures.
Keywords: cultural heritage; preservation approach; urban revitalisation; Belgrade waterfront